2019
DOI: 10.54530/jcmc.95
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Computed Tomography and Chest X-Ray Findings in Patient With Pulmonary Tuberculosis

Abstract: Background: Pulmonary Tuberculosis (PTB) is a major public health problem in Nepal. Diag­nosis of pulmonary tuberculosis is done by bacteriological confirmation of respiratory speci­men however Negative smear needs clinical and radiological evaluation for the diagnosis in suspected patient. This study focuses on radiological findings in both Pulmonary bacterio­logically confirmed (PBC) and pulmonary clinically diagnosed (PCD) Tuberculosis. Methods: This observational study was conducted at Chitwan Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Both the diagnostic tools have similar diagnostic potentials. 20 On the other hand, combined application of HRCT with serological testing has also been recommended for improved diagnosis of TB 21 . Previous research works have shown similar results for HRCT and interferon gamma releasing assay (IGRA), whereas, use of HRCT has been preferred over Gene Xpert.…”
Section: Discussionmentioning
confidence: 99%
“…Both the diagnostic tools have similar diagnostic potentials. 20 On the other hand, combined application of HRCT with serological testing has also been recommended for improved diagnosis of TB 21 . Previous research works have shown similar results for HRCT and interferon gamma releasing assay (IGRA), whereas, use of HRCT has been preferred over Gene Xpert.…”
Section: Discussionmentioning
confidence: 99%